Clinical and radiological characteristics of Mpox pneumonia in immunosuppressed HIV-infected patients: a multicenter study from China - Wang, Wei; Zhou, Zhongkai; Yuan, Chunwang; Wang, Fuxiang; Yin, Yue; Zhao, Lingling; Shi, Yanbin; Chen, Budong; Li, Hongjun (Frontiers in Microbiology, 2025)
BackgroundIn people living with HIV, particularly with low CD4+ T-cell counts, monkeypox virus (Mpox) can disseminate to visceral organs, leading to severe outcomes. Mpox pneumonia is a prominent severe phenotype, but systematic reports from China are scarce.MethodsThis multicenter retrospective study analyzed 41 HIV-infected patients with Mpox (June 2022–February 2025), divided into a pneumonia group (n = 21) and a control group (n = 20). Clinical, laboratory, and thin-section chest computed tomography (CT) findings, multisystem involvement, outcomes, and the roles of immune status and antiretroviral therapy (ART) adherence were compared.ResultsAll patients were men who have sex with men. Mpox pneumonia occurred almost exclusively in patients with CD4+ T-cell counts <200/μL. Thin-section CT revealed multiple, randomly distributed, well-demarcated, non-enhancing nodules (2–36 mm), consistent with hematogenous necrotizing lesions. All pneumonia cases had ≥2 organ systems involved (e.g., proctitis, necrotic skin lesions, intestinal obstruction, sepsis). Compared with controls, pneumonia patients showed more frequent inflammation and organ injury markers (elevated C-reactive protein, procalcitonin, D-dimer, creatinine, and anemia). The case fatality rate was 38.1% (8/21) in the pneumonia group versus 0% in controls. Patients with consistent ART recovered, whereas all deaths occurred in those untreated or with irregular ART adherence.ConclusionMpox pneumonia in HIV-infected individuals primarily affects those with advanced immunosuppression, presenting with disseminated necrotizing pulmonary nodules, multisystem involvement, and high mortality. Consistent ART markedly improves prognosis, highlighting the need for early identification of high-risk patients and integrated management—including sustained ART and targeted Mpox treatment—to reduce severe outcomes.